Admission Pattern of Newborns admitted in special newborn care unit: an observational from North West of India - Kumar, Girish; Sood, Abhilash; Sharma, Nivedita; Sharma, Vandana; Kumar, Amit (International Journal of Research in Medical Sciences, 2022)
Background: Globally, neonatal deaths constitute 44% of all deaths in less than 5 years age group .The concept of SNCU is based on the learning from the “Purulia model”. This research study was undertaken, to assess the profile of sick newborns admitted in the SNCU. Methods The investigators analyzed this data and establish the morbidity profile of newborns admitted in SNCU Hamirpur in 2019. Results: Total of 422 newborns were admitted 197 (46.7%) were females and 225 (53.3%) were males. Out of these 381 (90.3%) were inborn and 41(9.7%) were out born. In inborn 293 (76.9%) weighed more than 2.5 kg, 83 (21.8%) were low birth weight <2.5 kg to 1.5 kg and 2 (0.52%) were very low birth weight i.e < 1.5 kg to 1 kg and one newborn was extreme low birth weight i.e <1 kg. In the out born group, 23 (56.1%) weighed more than 2.5 kg and 13 (31.8%) were low birth weight <2.5 kg to 1.5 kg, 4 (9.8%) were very low birth weight < 1.5 kg to 1 kg. Jaundice was the most common neonatal condition 63%, infection 9.5%, respiratory diseases 9% and birth asphyxia 7.8%. Conclusions: The most sensitive time for morbidity and mortality development is during the newborn period. The main reasons for SNCU hospitalisation include neonatal jaundice, preterm, low birth weight, perinatal asphyxia, and infection. Neonatal Jaundice continues to be the primary reason for both inborn and outborn newborns admission to SNCU, and inborn babies make up the majority of this group.